Residential Energy Consumption for Space Heating in Norwegian Households A Discrete-Continuous Choice Approach - Runa Nesbakken (Statistics Norway, Research Department, 1998)
In this paper the demand for space heating energy is estimated by using a discrete-continuous choice model which focuses on the relationship between the choice of heating equipment and energy consumption. The model is estimated on Norwegian micro data, and the two stages of the model are estimated simultaneously. The capital cost and the operating cost of the heating systems are both found to have a significant impact on the choice of heating system. Furthermore, the results show that household characteristics are important variables in residential energy models. Energy price elasticities and income elasticities are estimated.
Keywords: C51; D12; Q41; 330; Household energy consumption; space heating system; discrete-continuous choice.